Heat Shock Protein HSP101 Affects the Release of Ribosomal Protein mRNAs for Recovery after Heat Shock . Issue 2 (5th April 2017) - Merret, Rémy; Carpentier, Marie-Christine; Favory, Jean-Jacques; Picart, Claire; Descombin, Julie; Bousquet-Antonelli, Cécile; Tillard, Pascal; Lejay, Laurence; Deragon, Jean-Marc; Charng, Yee-yung
Abstract : mRNAs coding for ribosomal proteins are preferentially stored during heat shock and released during recovery phase to enhance ribosome production in an HSP101-dependent manner. Abstract: Heat shock (HS ) is known to have a profound impact on gene expression at different levels, such as inhibition of protein synthesis, in which HS blocks translation initiation and induces the sequestration of mRNAs into stress granules (SG s) or P-bodies for storage and/or decay. SG s prevent the degradation of the stored mRNAs, which can be reengaged into translation in the recovery period. However, little is known on the mRNAs stored during the stress, how these mRNAs are released from SG s afterward, and what the functional importance is of this process. In this work, we report that Arabidopsis HEAT SHOCK PROTEIN101 ( HSP101 ) knockout mutant ( hsp101 ) presented a defect in translation recovery and SG dissociation after HS . Using RNA sequencing and RNA immunoprecipitation approaches, we show that mRNAs encoding ribosomal proteins (RP s) were preferentially stored during HS and that these mRNAs were released and translated in an HSP101-dependent manner during recovery. By 15 N incorporation and polysome profile analyses, we observed that these released mRNAs contributed to the production of new ribosomes to enhance translation. We propose that, after HS, HSP101 is required for the efficient release of RP mRNAs from SG s resulting in a rapid restoration of the translation machinery by producing new RP s.